(untitled) (Journal of Informatics and Mathematical Sciences, 2020)
This paper deals with the motion of infinitesimal mass around primaries whose are radiating and triaxial. They are moving around each other in elliptic orbits about the common barycenter in the neighborhood of collinear equilibrium points. It is observed that location and stability of collinear points are effected by radiation and triaxiality of primaries. The results shows that collinear points \(L_1\) and \(L_2\) are having unstable behavior, while \(L_3\) is showing stable behavior for some values of radiation and triaxiality.